PENGARUH PENGGUNAAN MODEL PENEMUAN KONSEP TERHADAP KEMAMPUAN MENGANALISIS MATERI SEJARAH SISWA KELAS X SMA NEGERI I SEPUTIH BANYAK - Wayan Lenni; Elis Setiawati (Swarnadwipa, 2017)
The purpose of this study was to determine the effect of the use of the concept of the invention models the ability to analyze the material history of the semester students of class X SMA Negeri I white as Many of the school year 2016/2017. The design used by researchers is the Quasi-Experiment with design type Nonquivalent control group design, sample using means cluster random sampling (sampling based on local population that has been set by the researchers), a test in class X IPS4 taken were 30 students, the experiment in class X IPS1 taken control of 30 students while in class X IPS3 taken is 31 students. Questions on the 45 tested a number of questions after it turned out that a valid validated 30 matter. So this study was no effect of the use of models to analyze the ability of the concept to the discovery of the historical material Class X SMA I Seputih Many second semester of academic year 2016/2017. Upon investigation it turns out there is the effect of the invention models the concept of the ability to analyze the historical material in class X IPS1.